Gambaran Kadar Kolesterol pada Akseptor Kontrasepsi Suntik - Pupung Cahya Wulandari; Surati Surati (Jaringan Laboratorium Medis, 2019)
Based on the population census data from 2016, there are more than 258 million people and it’s projected will continue grow. Family planning programs for family planning total and restriction on the use of contraceptive. The number of fertile age couple in the province of central java in 2016 was 6.727.894 of all fertile age couples of 78.6% active family planning participants. The type of contraception that is often used is injection at 54.2%. The most many used contraceptive injection is contraceptive injection 3 month (DMPA). In Semarang City, Pedurungan district the most number of fertile age couples. The village with the most injectable contraceptive acceptors is Tlogosari Kulon Village. Injectable contraception causes changes in fat metabolism through changes in cholesterol levels. Descriptive type research with cross sectional. The study sample was 25 injectable contraceptive acceptors 3 months. The result examination of cholesterol levels in injectable cholesterol levels in injectable contraceptive acceptors 3 months on average cholesterol levels is 209.5 mg/dl, as many 12 acceptor contraceptive injective 3 months had normal cholesterol levels (48%), and as many 13 acceptor contraceptive injective 3 months had above normal cholesterol levels (52%). 3 month injection contraception can increase cholesterol levels.